The use of tart cherry supplementation by sport science practitioners, sub-elite and elite athletes: practices and attitudes - Sabou, V.; Wangdi, T.; O`Leary, M.; Kelly, V.; Bowtell, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Tart cherry (TC) supplementation has been shown to accelerate post-exercise recovery, enhance endurance performance and improve sleep duration and quality. The efficacy of dietary supplements depends on using an effective supplementation protocol, which may not always be the case in applied practice. Therefore we investigated the use of TC supplementation by sport science practitioners, sub-elite and elite athletes and compared this use to evidence based practice.